Workspace exploration and protection with multiple robots assisted by sensor networks. (9th August 2018) - Kim, Jonghoek
This article introduces multi-robot strategies making multiple robots explore an unknown environment in a cooperative manner. Our exploration strategies do not require global localization of a robot or a node. Multiple robots build a Voronoi diagram as a topological map of the environment, while deploying sensor nodes which can sense and communicate. As the sensor network built by one robot meets the network built by another robot, both robots can exchange data with each other. The robots then use the merged sensor network to protect the environment. We introduce an intruder capture algorithm assuming that a robot is able to access any intruder's location utilizing the sensor network. This algorithm is robust to time delay in information sharing utilizing the sensor network. Utilizing the algorithm, we derive upper bounds on the number of robots needed to capture every intruder in the environment. This article proves that the minimum number of robots needed can be computed by finding proper edge covers of the dual graph of the Voronoi diagram.